Carbon Cloth: High Areal Capacity Dendrite‐Free Li Anode Enabled by Metal–Organic Framework‐Derived Nanorod Array Modified Carbon Cloth for Solid State Li Metal Batteries (Adv. Funct. Mater. 2/2021). (11th January 2021) - Wang, Tian‐Shi; Liu, Xiaobin; Wang, Yu; Fan, Li‐Zhen
Abstract : In article number 2001973, Li‐Zhen Fan and co‐workers report a carbonized metal–organic framework nanorod modified carbon cloth for stable lithium metal anodes. Benefiting from the advantages of an interconnected carbon‐based skeleton and lithiophilic nanostructured layer, the NRA‐CC electrode provides significant improvements in electrochemical performance and safety, which provides fresh insight into the design principles of a dendrite‐free Li metal anode.